Mercadillos de agricultor en Tenerife: soberanía alimentaria y transición agroecológica - Huguet Gené, Júlia (2023)
Farmers’ market is a phenomenon that represents an alternative model of production, commercialization and consumption in contrast with the global dynamics of monocultural-oriented production and supermarket commercialization. This model, usually defined in the theory as a space based in small-scale, territorialized, family and proximity-based agriculture, can be potentially transformative and foster dynamics of food sovereignty and agroecological transition depending on its interconnections with the socio environmental context. The case of Tenerife, as in the other Canary Islands, is paradigmatic due to the high number of farmers' markets that still exist today in comparison with the decline and disappearance that are experiencing worldwide, as well as the significant presence of farmers who are opting for a more economically, socially and environmentally friendly way of producing and commercializing their products. The main research question is if farmers’ markets are drivers for agroecological transition and food governance. In accordance with the interrelation between the different spheres of production-commercialization-consumption, the main goal of the research is analyze the current state of agroecological transition on the island of Tenerife in the three dimensions and/or scales that make up agroecology: in the ecological-productive dimension analyzing the agroecological production at farm level, in the socio-cultural dimension analyzing governance and consumption in the farmers' markets, and the socio-political dimension with an approximation to the public policies in force in the agricultural sphere. Therefore, fieldwork is currently being carried out to answer the research question exposed, using qualitative (semi-structured interviews, informal conversations and observation) and quantitative (geo-referencing and statistics) methods. In brief, it is expected that the results of this research will determine the current state of agroecological transition on the island of Tenerife, analyzing the role of short food supply chains models in promoting this change towards a fairer, more sustainable and resilient model.